Closure to Discharge Capacity of Labyrinth Side Weir Located on a Straight Channel by M. Emin Emiroglu, Nihat Kaya, and Hayrullah Agaccioglu - Emiroglu, M. Emin; Kaya, Nihat; Agaccioglu, Hayrullah (Asce-Amer Soc Civil Engineers, 2011)
[Abstract Not Available]